Influence of Perinatal, Postnatal and Hereditary Factors on Occurrence of Overweight and Development of Obesity in Children and Adolescents - T.V. Kobets; V.V. Yakovenko (Zaslavsky O.Yu., 2012)
The influence of perinatal (pathological course of pregnancy, delivery, fetation), postnatal (nutrition of infants in the first year of life, allergic history, age of onset and duration of disease) and hereditary factors (incidence of type 2 diabetes mellitus and hypertension) on the occurrence of overweight and development of obesity in children and adolescents had been studied.